(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Introduction: Wilms tumor is the most common primary malignant renal tumor of childhood. It is important to pick up the children with wilms tumor earlier as early stages has excellent outcomes after treatment. Objective : To find out the common clinical presentations and pathological profile of Wilms tumor in children. Methods and Materials : A hospital based prospective study done with twenty diagnosed patients of Wilms tumour enrolled from department of Pediatric haemato-oncology, BSMMU, Dhaka in the period between January to December 2008. Results- The peak incidence of Wilms tumor was in 1 to 5 years age group (80%,n=16). Median age at presentation was 49 months with male: female ratio 1.8:1.The most common presentation was abdominal swelling (80%,n=16),followed by flank mass (75%,n=15), abdominal pain (55%,n=11), haematuria (15%,n=3), hypertension (10%,n=2). Thirteen raised from right kidney, ratio of right to left involvement 1.8:1. Histologically 13(65%) patients had triphasic histology having blastemal, stromal and epithelial elements, 7(35%) was biphasic having blastema and epithelia. All had favourable histological pattern. Most patients presented in stage III (55%,n=11) followed by stage II (25%,n=5), Stage IV(10%,n=2), Stage I(10%,n=2). No bilateral presentation. Conclusions : Most of the patients of Wilms tumor presented within 1 to 5 years of age(80%) with abdominal distension(80%) and flank mass(75%), few associated with haematuria(15%) and hypertension(10%). Histologically all were favourable and maximum presented in stage III (55%) followed by stage II(25%). DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21015 J Bangladesh Coll Phys Surg 2014; 32: 5-8